External Debt and Worsening Business Cycles in Less Developed Countries - LEUNG, Hing-Man (Institutional Knowledge at Singapore Management University, 2003)
Less developed countries (LDCs) have seen considerable business cycles in recent decades. At the same time they have significantly increased their external-debt-to-GDP ratios. It seems natural to suspect that increased indebtedness and the amplified cycles are linked. The paper presents a simple macroeconomic model to formalize this connection. External debt is the novelty of this model. The paper's main contribution is to calibrate the dynamic parameter using the World Development Indicator. It is found that the LDC dynamic behavior is generally non-oscillatory. Alarmingly though, the dynamic convergent system in the 1970s has been replaced by one of divergence.